Perception of the McGurk effect in people with one eye depends on whether the eye is removed during infancy or adulthood - Moro, Stefania S.; Qureshi, Faizaan A.; Steeves, Jennifer K. E. (Frontiers in Neuroscience, 2023)
Background: The visual system is not fully mature at birth and continues to develop throughout infancy until it reaches adult levels through late childhood and adolescence. Disruption of vision during this postnatal period and prior to visual maturation results in deficits of visual processing and in turn may affect the development of complementary senses. Studying people who have had one eye surgically removed during early postnatal development is a useful model for understanding timelines of sensory development and the role of binocularity in visual system maturation. Adaptive auditory and audiovisual plasticity following the loss of one eye early in life has been observed for both low-and high-level visual stimuli. Notably, people who have had one eye removed early in life perceive the McGurk effect much less than binocular controls. Methods: The current study investigates whether multisensory compensatory mechanisms are also present in people who had one eye removed late in life, after postnatal visual system maturation, by measuring whether they perceive the McGurk effect compared to binocular controls and people who have had one eye removed early in life. Results: People who had one eye removed late in life perceived the McGurk effect similar to binocular viewing controls, unlike those who had one eye removed early in life. Conclusion: This suggests differences in multisensory compensatory mechanisms based on age at surgical eye removal. These results indicate that cross-modal adaptations for the loss of binocularity may be dependent on plasticity levels during cortical development.